2013
DOI: 10.1371/journal.pone.0071986
|View full text |Cite|
|
Sign up to set email alerts
|

Soil Respiration and Organic Carbon Dynamics with Grassland Conversions to Woodlands in Temperate China

Abstract: Soils are the largest terrestrial carbon store and soil respiration is the second-largest flux in ecosystem carbon cycling. Across China's temperate region, climatic changes and human activities have frequently caused the transformation of grasslands to woodlands. However, the effect of this transition on soil respiration and soil organic carbon (SOC) dynamics remains uncertain in this area. In this study, we measured in situ soil respiration and SOC storage over a two-year period (Jan. 2007–Dec. 2008) from fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
16
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 69 publications
4
16
0
2
Order By: Relevance
“…2) and increased by 7-46% following the conversion of cropland to woodland and grassland, which was in line with previous studies (Frank et al, 2006;Jenkins and Adams, 2010;Wang et al, 2013). This may likely be related to the increase in SOC content and fine root biomass.…”
Section: Biotic Factors Influencing Soil Respiration Among Land-use Csupporting
confidence: 90%
See 1 more Smart Citation
“…2) and increased by 7-46% following the conversion of cropland to woodland and grassland, which was in line with previous studies (Frank et al, 2006;Jenkins and Adams, 2010;Wang et al, 2013). This may likely be related to the increase in SOC content and fine root biomass.…”
Section: Biotic Factors Influencing Soil Respiration Among Land-use Csupporting
confidence: 90%
“…In recent years, considerable effort has been made to understand the influence of the conversion of native forest to cropland or grassland in tropical and subtropical regions (Adolfo Campos, 2006;Fernandes et al, 2002;Sheng et al, 2010) and in temperate regions (Arevalo et al, 2010). Some other studies have also investigated the influence of the conversion between woodland and grassland in temperate regions (Smith and Johnson, 2004;Wang et al, 2013). However, to our knowledge, few studies have focused on the conversion of cropland to woodland or grassland in degraded ecosystems (Rey et al, 2011;Shi et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…While afforestation of moorland increased Rs, afforestation of grassland significantly reduced Rs. A number of previous studies reported reductions in Rs upon afforestation of pasture and cropland ScottDenton et al, 2006;Hiltbrunner et al, 2012Hiltbrunner et al, , 2013Wang et al, 2013;Zhang et al, 2013) that was attributed to low C inputs from tree to belowground communities. This observation is consistent with a previous report of considerably lower primary production and soil respiration in forest compared with grassland at the field scale (Schulze et al, 2010).…”
Section: Land Use Impact On Soil Respiration and Microbial Community mentioning
confidence: 97%
“…Generally, the Rs rate varied seasonally; Rs began to increase in the spring when temperature began to increase, reached its peak value during summer, and decreased thereafter. Such variation has been reported to be attributable to changes in Ts (Koizumi et al, 1999;Buchmann, 2000;Suh et al, 2006;Wang et al, 2013).…”
Section: Soil Respiration Ratementioning
confidence: 97%